The Role of Information When Forming Professional Self-Determination of School-Children - Jankevičius, Stasys (Acta Paedagogica Vilnensia, 2001)
The analysis of different concepts of activity motivation and their generalization allows us to affirm that for the motivation of choosing profession the most suitable is the model of decision upon importance of the aim to be achieved and of the importance of the realization of this aim. The first determinant comprises two interconnected determinants: the probabilities of the motives and professional values existing at the basis of these motives; the second determinant comprises critical evaluation of the essential probable conditions of conscious professional self-determination. Both determinants are formed by information received by way of personal experience, as well as by means of pedagogical influence. At least three conditions are possible which help to turn subjective decision in the direction of objectivity. The decision of choosing profession will be more objective if, firstly, the school child has mare fully realized essential professional values, secondly, if his evaluation compromises more probable conditions for reasonable self-determination and, thirdly, if the chooser gets comprehensive information which forms his ability to evaluate.
Keywords: Activity motivation; choice of profession; professional values; professional self-determination.